18. yy. şairi asaf ve divanı (inceleme- tenkitli metin- dizin) cilt:1 - Kaya, Hasan (My University, 2009)
18. Yüzyıl Şairi Âsaf ve Dîvânı (İnceleme-Tenkitli Metin-Dizin) adlı doktora tezinde şair Âsaf’la ilgili tespitler yapılmış, şairin sanat yönü değerlendirilmiş ve iki nüshası olan Dîvânı’nın bilimsel yöntemlerle tenkitli metni hazırlanmıştır. Tez üç bölümden oluşmaktadır. Birinci bölümde hakkında herhangi bir kayıt bulunmayan, Süleymaniye Kütüphanesi Fatih Kitaplığı Bölümü 3778 ve Topkapı Sarayı Müzesi Kütüphanesi Hazine Kitaplığı Bölümü 874 numarada kayıtlı Dîvân’ın şairi Âsaf’ın eserinden hareketle hayatı hakkında bir değerlendirme yapılarak Sultan III. Ahmet (1703-1730) dönemi şairlerinden olduğu ortaya konmuş ve edebî kişiliği incelenmiştir. İkinci bölümde Âsaf Dîvânı şekil ve muhtevâ özellikleri bakımından değerlendirilmiştir. Şekil özelliklerinde şairin vezin, nazım şekli, âhenk ve sanat anlayışı hakkında değerlendirmeler yapılmıştır. Muhtevâ özellikleri ortaya konurken hemen hemen tahlil çalışmalarında yer alan bütün konular etrafında eser incelenmiş, özellikle sosyal hayat ve tabiatla ilgili konularda detaylı bir çalışma yapılmıştır. Üçüncü bölüm Âsaf Dîvânı’nın tenkitli metninin ve özel adlar dizininin yer aldığı bölümdür. Tenkitli metinden önce nüshalar tanıtılmış ve metnin kurulmasında izlenen yol ortaya konmuştur. Bu tezle, iki nüshası olan ve içerisinde 1218 şiir bulunan Dîvân’ın metninin ortaya konması, şairin edebî yönünün değerlendirilmesi ve hakkında hiçbir bilgi bulunmayan Âsaf’ın hangi dönem şairi olduğunun belirlenmesi, Türk edebiyatında gazel ve nazîre şairi olarak anılması, bunun yanında 18. Yüzyılın ilk yarısında klâsik şiirimizle ilgili yapılacak inceleme ve değerlendirme çalışmalarına kaynak sağlanması amaçlanmıştır.

In this doctorate thesis titled as 18th Century Poet Asaf and His Divan (The Study-An Edition Critical Text-Index), some statements were made about poet Asaf, his artistic properties were assessed and an edition critical text was prepared with scientific methods for his Divan, which has two copies. The thesis consists of three parts. In the first part, the literary personality of the poet, about whom there aren’t any written records, was brought to light based on the evaluations made about his period and his life and it was pointed out that he was one of the poets belonging to the period of Sultan Ahmed III and the poet’s literary personality was analyzed. His Divan has got two copies. One of them is registered with the number 3778 in Süleymaniye Library Fatih Books Department and the other copy is registered with the number 874 in Topkapı Palace Museum Library Treasure Books Department. In the second part, Asaf’s Divan was analyzed in terms of form and content. In the form properties part, some evaluations were made about that poet’s prosody, style of versification, harmony and artistic perception. While content the properties of Divan were being studied, it was examined in terms of almost all the subjects that can be found in the analytical research and a detailed study was carried out about especially the period’s social life and natural subjects. The third part is the index of personal names and the edition critical text of Asaf’s Divan. Before the edition critical text, the copies of the Divan were introduced and the method was explained as to how the text was formed. With this thesis, it is aimed to introduce the Divan’s text, which has two copies and contain 1218 poems, to evaluate the artistic aspect of the poet, to determine which period the poet, about whom there aren’t any written records, belongs to, to make the poet known as a ghazel and nazire poet in the Turkish Literature. And it’s also aimed to provide a written source for searching and evaluating studies about the classic poetry in the first half of 18th Century.
Keywords: Divan Şiiri; Türk Dili